Peran Dukungan Keluarga dalam Meningkatkan Kesejahteraan Emosional Siswa Kelas V di SDN 1 Gunungrejo - Amellia Isa Nabila Puri Safitri; Devi Wahyu Ertanti (Mathematics Education Study Program, 2025)
This study examines the emotional well being of fifth grade students at SDN 1 Gunungrejo, focusing on the impact of family support on their psychological and academic development. The objective is to explore the experiences of students regarding the emotional support they receive from their families and teachers. Employing a qualitative approach with grounded theory methodology, data were collected from 20 students through surveys and interviews with two teachers, including the homeroom teacher and an Islamic religion teacher. The survey was divided into two sections: one measuring family support and the other assessing students' emotional well-being. The findings revealed that 95% of students reported receiving strong emotional support from their families, with 90% expressing overall life satisfaction. However, 70% of students indicated experiencing stress due to academic pressures. These results highlight the crucial role of family support in enhancing students' self-confidence and motivation while indicating that insufficient emotional support can negatively affect students' mental health. The study concludes that active parental involvement and teacher support are essential to promoting students' emotional well-being and creating a positive educational environment.